2015
DOI: 10.1002/gps.4318
|View full text |Cite
|
Sign up to set email alerts
|

Daytime somnolence as an early sign of cognitive decline in a community‐based study of older people

Abstract: Objective This study aimed to examine the association between self-reported sleep problems and cognitive decline in community-dwelling older people. We hypothesized that daytime somnolence predicts subsequent cognitive decline. Methods This is a longitudinal study in a 3.2-year follow-up, with 18-month intervals. The setting is the Washington Heights-Inwood Community Aging Project. There were 1098 participants, who were over 65 years old and recruited from the community. Sleep problems were estimated using f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
35
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 68 publications
(96 reference statements)
5
35
1
1
Order By: Relevance
“…An alternative explanation of our findings is that both SCD and sleep dysregulation are initial symptoms of an undetected subclinical neurodegenerative disease. Indeed, MCI and dementia—especially AD—have both been associated with increased sleep dysregulation (Lim, Kowgier, Yu, Buchman, & Bennett, ; Tsapanou, Gu, Manly, et al., ; Tsapanou, Gu, O'Shea, et al., ), and existing literature points to the presence of AD biomarkers in adults expressing SCD. Overall, therefore, although we were careful to exclude subjects with dementia or even MCI, and to additionally adjust for objective cognition, we cannot fully exclude the possibility that both sleep problems and the self‐perception of the cognitive performance could still be an indication of preclinical cognitive alterations that could lead to future dementia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An alternative explanation of our findings is that both SCD and sleep dysregulation are initial symptoms of an undetected subclinical neurodegenerative disease. Indeed, MCI and dementia—especially AD—have both been associated with increased sleep dysregulation (Lim, Kowgier, Yu, Buchman, & Bennett, ; Tsapanou, Gu, Manly, et al., ; Tsapanou, Gu, O'Shea, et al., ), and existing literature points to the presence of AD biomarkers in adults expressing SCD. Overall, therefore, although we were careful to exclude subjects with dementia or even MCI, and to additionally adjust for objective cognition, we cannot fully exclude the possibility that both sleep problems and the self‐perception of the cognitive performance could still be an indication of preclinical cognitive alterations that could lead to future dementia.…”
Section: Discussionmentioning
confidence: 99%
“…We could hypothesize that sleep problems may be causing more SCD. Poor sleep quality has been associated with low cognitive performance, especially in the elderly (Tsapanou, Gu, Manly, et al, 2015;Tsapanou, Gu, O'Shea, et al, 2015;Yaffe et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sleep problems are common among the elderly population [1] and have been linked to many disorders in the specific age group [2-4]. In particular, sleep disordered breathing (SDB) – including difficulties breathing during sleep- has a high prevalence among older adults, and often occurs even with atypical symptoms [5, 6].…”
Section: Introductionmentioning
confidence: 99%
“…At the outset the authors argue that many laboratory studies in young healthy adults have shown that napping is good for memory and alertness, so it may be expected that those older people who nap perform better and are more alert. This expectation is countered by epidemiological studies showing that naps, and in particular long naps, are associated in general with poor health, mortality and cognitive decline (Tsapanou et al ., ; Yamada et al ., ). The data of the present study are clear: nappers are more sleepy, have a higher body mass index and a higher cumulative illness rating than non‐nappers.…”
mentioning
confidence: 97%